A Literature Review on Intellectual Property Protection - Xinyi, Hu (Transactions on Economics, Business and Management Research, 2024)
This literature review examines the significance, challenges, and strategies for intellectual property (IP) protection in the context of globalization and technological advancements. It highlights the importance of IP protection in promoting innovation, maintaining market order, and safeguarding consumer rights. The review discusses challenges such as cross-border infringement, emerging technological threats, and lagging legal systems. It also explores strategies to address these challenges, including international cooperation, legal reform, public awareness-raising, and technological innovation. The paper concludes that a comprehensive and adaptive approach is essential to ensure that IP protection remains effective in the digital age, fostering creativity, competition, and progress.